The relationship of job motivation toward job satisfaction among executive of Transmission Division at Tenaga Nasional Berhad (Dua Sentral Branch) / Nur Aqilah Abdul Latif - Abdul Latif, Nur Aqilah (Faculty of Business and Management, 2013)
The study investigates the relationship between Job Motivation and Job Satisfaction. Job Motivation has been treated as an independent and Job Satisfaction as dependent variable. This study was conducted at Tenaga Nasional Berhad of Dua Sentral Branch, Kuala Lumpur. In completing this research, about 118 questionnaires have been distributed to the respondents and only 113 were return back. The primary data has been collected by the researcher through a questionnaire and based on five pointer Likert scale. The respondent are included the executive level employees from five of the ten department from Transmission Division at Tenaga Nasional Berhad of Dua Sentral. The five departments that have been involved in this research are Human Resource Management and Administrative Services Departments,Asset Management of Central Department, Asset Management of Kuala Lumpur Department, Chief Engineer of Major Project Department, and Asset Development Department. In order to get result for the study, the researcher has used SPSS Version 20.0 program to analyze the data from the information gathered. To analyze the data, the researcher has used reliability analysis, cross tabulat ion analysis, frequency distribution analysis and descriptive statistic by using SPSS program. From the finding, the researcher indicates that there are a positive relationship between job motivation and job satisfaction.